(untitled) (Journal of Bangladesh College of Physicians and Surgeons, 2026)
Dengue is a common but potentially deadly illness, which can be complicated by hemophagocytic lymphohistiocytosis (HLH). This report describes two cases of dengue fever in otherwise healthy individuals who faced challenges due to HLH. The diagnosis was established by meeting the clinical and laboratory criteria for HLH. Both patients were successfully treated with a pulse regimen of methylprednisolone and other supportive measures. This case report highlights the importance of early diagnosis and appropriate treatment for HLH patients to reduce morbidity and mortality associated with this condition. J Bangladesh Coll Phys Surg 2026; 44: 68-71